Exploring the antibacterial and anti-biofilm activity of two Iranian medical-grade kinds of honey on multidrug-resistant Pseudomonas aeruginosa - Mustafa Riyadh Alshaybawee; Shahrzad Asgari; Paria Ghadersoltani; Ahmadreza Mehrabian; Parastoo Saniee (BMC Complementary Medicine and Therapies)
Abstract Introduction Pseudomonas aeruginosa is a prominent multidrug-resistant and biofilm-forming bacteria. Mono-floral honey, enriched with a variety of biological compounds, can be categorized as medical-grade honey due to its notable pharmacological benefits. In this study, two types of Iranian honey were thoroughly characterized, and the antimicrobial and anti-biofilm properties were examined against three clinical strains of multidrug-resistant P. aeruginosa. Methods Citrus and Thyme honey from Alborz were selected based on physicochemical, phytochemical, and melissopalynological tests conducted from a medical perspective. The antibacterial activity of the honey samples against three clinical strains of multidrug-resistant P. aeruginosa isolated from wound infections was evaluated using both the well-diffusion and broth microdilution methods. Additionally, an antibiofilm assay was performed using the crystal violet method in microplates. Results Both medical grade honey samples exhibited considerable antibacterial activity against the three P. aeruginosa isolates at 75–100% v/v concentrations with inhibition zones measuring between 15 and 30 mm. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) values for both types of honey were 6.25% v/v (final concentration). The antibiofilm assay indicated that both types of honey demonstrated varying levels of antibiofilm activity. Citrus honey at 9% concentration was the most effective, showing an average inhibition rate of 59%, while Citrus honey at 2.3% final concentration exhibited the least effectiveness with an average inhibition rate of 23%. Discussion A thorough analysis of the honeys studied confirmed their authenticity and the presence of medicinal compounds. The results of honey tests correspond to the normal range (natural Honey) in the Council of the European Union. Based on the evaluation and compliance with the medical grade criteria including authenticity, health, qualities well botanical origin mentioned honey is classified in medical grade. The antibacterial results indicated that both Thyme and Citrus honeys effectively inhibit the growth and biofilm formation of P. aeruginosa. Therefore, these honeys may serve as natural and safe alternatives or adjuncts to conventional antibiotic therapy for wound healing and infection management.